2003
DOI: 10.1108/eb058411
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives of satisfaction research in tourism destinations

Abstract: The paper presents important measurement approaches in the field of costumer satisfaction with services and applies those empirically for service bundles at the level of the tourism destination. After working out the most prominent characteristics of existing satisfaction concepts according to the American and the Scandinavian school of thought, the latter will be critically evaluated for its potential practical use in measuring guest satisfaction. Based on this preparatory work, the Importance‐Performance Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 25 publications
1
75
0
5
Order By: Relevance
“…(Fuchs & Weiermair, 2003). According to Destination image is an interactive system of thoughts, opinions, feelings, visualizations, and intentions toward destination (p. 200).…”
Section: Destination Image In Relation To Tourist Satisfactionmentioning
confidence: 99%
“…(Fuchs & Weiermair, 2003). According to Destination image is an interactive system of thoughts, opinions, feelings, visualizations, and intentions toward destination (p. 200).…”
Section: Destination Image In Relation To Tourist Satisfactionmentioning
confidence: 99%
“…In this sense, previous researches have examined factors influencing tourist behavior towards a repeat visitation. In tourism, major antecedents of revisit intention such as satisfaction (Baker & Crompton, 2000;Frochot & Hughes, 2000;Kozak, 2001Kozak, , 2003Petrik et al, 2001;Yuksel, 2001;Fuchs & Weiermair, 2003;Fallon & Schofield, 2003;Li & Carr, 2004;Jang & Feng, 2007), novelty seeking (Jang & Feng, 2007), perceived value (Petrik et al, 2001;Um et al, 2006;Chen & Tsai, 2007;Bigne et al, 2009), past vacation experience (Chen & Gursoy, 2001;Kozak, 2001;Petrik et al, 2001), safety (Chen & Gursoy, 2001), cultural differences (Reisinger & Turner, 1998;Chen & Gursoy, 2001), image (Ross, 1993;Milman & Pizam, 1995;Yoon & Uysal, 2005, Chi & Qu, 2008, motivation and satisfaction (Yoon & Uysal, 2005), and destination attributes (Akama, 2003;Chi & Qu, 2008;Zabkar et al, 2010) have been identified by various researchers. Chen & Tasi (2007) assert that "by understanding the relationships between future behavioral and its determinants, destination tourism managers would know better on how to build up an attractive image and improve their marketing efforts to maximize their use of resources" (p. 1116).…”
Section: Introductionmentioning
confidence: 99%
“…This study was an endeavour wherein it was implacable for the first time to know how the visitors can enhance the growth of hospitality industries through their self-planned tour. It has been well-known that the growth of hospitality industries in the tourist spots increase revenue generations and employment opportunities [21], [26]- [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, service quality is the consumer's evaluation of the perceived quality, instead of their satisfaction with an incident or transaction [14]. Many researchers have suggested that service quality performance could be an appropriate measure to test tourist satisfaction, because the tourist is likely to be satisfied, when a product or service performance is at a desired level [10], [14]- [21]. In the tourism sector, service quality can be regarded as the tourists' judgment about a product or service overall excellence or superiority [22]- [23].…”
Section: Introductionmentioning
confidence: 99%